BRAND REGISTRATION PROCEDURE AND PROCESS TS DESSERT CASTLE AS A LEGAL PROTECTION OF INTELLECTUAL PROPERTY - Puteri Ariesta Nadia; Agustianto Agustianto (Universitas Internasional Batam, 2022)
The article entitled TS Dessert Castle Mark Registration Procedure and Process as an Effort to Protect Intellectual Property Law is motivated by the presence of increasingly creative and mushrooming businesses in Indonesia. These businesses are growing rapidly, one of which is the cafe business. A cafe is a place that is usually used to enjoy food and drinks, but each comes with its own uniqueness. This uniqueness can be an identity that distinguishes one cafe from another. This identity is also expressed in a brand. Trademarks should have legal protection. Therefore, the author would like to reveal the procedures and process of trademark registration for cafe business actors in Batam City, which in this case is together with one of the business actors named TS Dessert Castle. Where Batam City is a potential area so that currently there are many cafe businesses that stand in the city. This study aims to produce an understanding or education about the importance of registering a trademark for Batam City cafe business actors. Based on the results of the study, it can be concluded that Indonesia itself actually already has regulations regarding trademark protection, namely the Trademark Law No. 20 of 2016. Further studies are needed on trademark registration research in the form of case studies so that it can be used as a reference for other business actors, regarding the importance of registering brand.